Red emitting Eu:ZnO nanorods for highly sensitive fluorescence intensity ratio based optical thermometry. Issue 5 (16th January 2017) - Senapati, S.; Nanda, K. K.
Abstract : Red emitting Eu:ZnO nanorods for highly sensitive optical ratiometric temperature sensing by following the fluorescence intensity ratio technique. Abstract : Here, we report the synthesis of Eu:ZnO nanorods by a hydrothermal method and their use as fluorescence intensity ratio (FIR) based optical temperature sensors. The as-prepared nanorods show band to band UV emission along with Eu 3+ emissions accompanied by broad intense visible host defect related emissions under UV (355 nm) excitation, whereas only Eu 3+ related emissions are observed under visible (532 nm) excitation. The emissions corresponding to 5 D1, 5 D0 → 7 F1 and 5 D1, 5 D0 → 7 F2 under 532 nm excitation are considered for FIR based temperature sensing as 5 D1 and 5 D0 bands are very close to each other and can possess a thermal equilibrium between them. The intensity ratio between these transitions follows a Boltzmann type distribution function. The sensitivity obtained by fitting the intensity ratio is very high (3013/ T 2 K −1 for 5 D1, 5 D0 → 7 F2 ) as compared to the reported values for Eu 3+ based sensors and can be applied in a wide range of temperatures (83–493 K). The sensitivity is highly influenced by the doping concentration of Eu, increases with doping up to a certain extent and then decreases.